Subjective valuation of cushioning in a human drop landing task as quantified by trade-offs in mechanical work - Skinner, Nathaniel E.; Zelik, Karl E.; Kuo, Arthur D. (Journal of biomechanics, 2015)
Humans can perform motor tasks in a variety of ways, yet often favor a particular strategy. Some factors governing the preferred strategy may be objective and quantifiable, (e.g. metabolic energy or mechanical work) while others may be more subjective and less measurable, (e.g. discomfort, pain, or mental effort). Subjectivity can make it challenging to explain or predict preferred movement strategies. We propose that subjective factors might nevertheless be characterized indirectly by their trade-offs against more objective measures such as work. Here we investigated whether subjective costs that influence human movement during drop landings could be indirectly assessed by quantifying mechanical work performed. When landing on rigid ground, humans typically absorb much of the collision actively by bending their knees, perhaps to avoid the discomfort of stiff-legged landings. We measured how work performed by healthy adults (N=8) changed as a function of surface cushioning for drop landings (fixed at about 0.4m) onto varying amounts of foam. Landing on more foam dissipated more energy passively in the surface, thus reducing the net dissipation required of subjects, due to relatively fixed landing energy. However, subjects actually performed even less work in the dissipative collision, as well as in the subsequent active, positive work to return to upright stance (approximately linear decrease of about 1.52J per 1cm of foam thickness). As foam thickness increased, there was also a corresponding reduction in center-of-mass vertical displacement after initial impact by up to 43%. Humans appear to subjectively value cushioning, revealed by the extra work they perform landing without it. Cushioning is thus worth more than the energy it dissipates, in an amount that indicates the subjective discomfort of stiff landings.